Maquinarias deconstructivas : poesía y juego en Juan Luis Martínez, Diego Maquieira y Rodrigo Lira - Rioseco, Marcelo, 1967- (Serie Ensayo (Editorial Cuarto Propio). Literatura., 2013)
Investigates and analyzes the various innovations, contributions and forms of writings of the Chilean poets Juan Luis Martínez, Diego Maquieira, and Rodrigo Lira. The works of these authors are explored in detail through the perspective of game theory.